Immunoglobulin G production in COVID-19 - associations with age, outcome, viral persistence, inflammation and pro-thrombotic markers. Issue 3 (March 2023) - Pirabe, Anita; Schrottmaier, Waltraud C.; Heber, Stefan; Schmuckenschlager, Anna; Treiber, Sonja; Pereyra, David; Santol, Jonas; Pawelka, Erich; Traugott, Marianna; Schörgenhofer, Christian; Seitz, Tamara; Karolyi, Mario; et al.
Abstract: Age represents the major risk factor for fatal disease outcome in coronavirus disease (COVID-19) due to age-related changes in immune responses. On the one hand lymphocyte counts continuously decline with advancing age, on the other hand somatic hyper-mutations of B-lymphocytes and levels of class-switched antibodies diminish, resulting in lower neutralizing antibody titers. To date the impact of age on immunoglobulin G (IgG) production in response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is unknown. Therefore, we investigated the impact of age on the onset of IgG production and its association with outcome, viral persistence, inflammatory and thrombotic markers in consecutive, hospitalized COVID-19 patients admitted to the Clinic Favoriten (Vienna, Austria) between April and October 2020 that fulfilled predefined inclusion criteria. Three different IgGs against SARS-CoV-2 (spike protein S1, nucleocapsid (NC), and the spike protein receptor binding domain (RBD)) were monitored in plasma of 97 patients upon admission and three times within the first week followed by weekly assessment during their entire hospital stay. We analyzed the association of clinical parameters including C-reactive protein (CRP), D -dimer levels and platelet count as well as viral persistence with the onset and concentration of different anti-SARS-CoV-2 specific IgGs. Our data demonstrate that in older individuals anti-SARS-CoV-2 IgG production increases earlier after symptom onset and that deceased patients have the highest amount of antibodies against SARS-CoV-2 whereas intensive care unit (ICU) survivors have the lowest titers. In addition, anti-SARS-CoV-2 IgG concentrations are not associated with curtailed viral infectivity, inflammatory or thrombotic markers, suggesting that not only serological memory but also other adaptive immune responses are involved in successful viral killing and protection against a severe COVID-19 infection.